2021
DOI: 10.1007/s00192-021-05028-x
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal pelvic floor muscle training and urinary incontinence: a randomized controlled 7-year follow-up study

Abstract: Introduction and hypothesis Urinary incontinence is common postpartum. Our aims were to assess whether antenatal exercise including pelvic floor muscle training (PFMT) has long-term effects on urinary incontinence (UI) and to explore factors associated with UI 7 years postpartum. Methods A follow-up of a two-centre randomized controlled trial performed at St. Olavs Hospital and Stavanger University Hospital, Norway. In the original trial women were randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…After the initial screening, duplicate studies were excluded, and the remaining studies were subjected to title and abstract analysis. Five publications [19][20][21][22][23] were considered eligible for full review (Figure 1). However, one of the research groups 20 submitted three publications, 20,22,23 which reported results from different times, therefore these publications was considered as one study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After the initial screening, duplicate studies were excluded, and the remaining studies were subjected to title and abstract analysis. Five publications [19][20][21][22][23] were considered eligible for full review (Figure 1). However, one of the research groups 20 submitted three publications, 20,22,23 which reported results from different times, therefore these publications was considered as one study.…”
Section: Resultsmentioning
confidence: 99%
“…Five publications [19][20][21][22][23] were considered eligible for full review (Figure 1). However, one of the research groups 20 submitted three publications, 20,22,23 which reported results from different times, therefore these publications was considered as one study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2021), ispitujući dugoročni efekat prenatalnog vježbanja na urinarnu inkontinenciju i faktore povezane s njom sedam godina nakon porođaja, utvrdili su prevalencu SUI 35% (298/855) kod 78 učesnica (51%) u interventnoj grupi i 63 (57%) u kontrolnoj grupi (p = 0,539). Dugoročno praćenje interventne grupe potvrdilo je da smanjen intenzitet vežbanja pet puta više povećava šansu za razvoj SUI (OR 5,4, 95% CI 2,6, 11,5) (22).…”
Section: Rezultatiunclassified